2022
DOI: 10.1108/ci-10-2021-0194
|View full text |Cite
|
Sign up to set email alerts
|

A guiding model for developing construction training programmes focusing on productivity and performance improvement for different qualification levels

Abstract: Purpose The effectiveness of the construction industry highly depends on the quality of the work practices, education and training. Based on the industry’s need to strengthen the productivity and performance improvement scopes in the construction education/training practices, this study aims to develop a guiding tool for designing new training programmes in different qualification levels considering the industry’s near-future challenges. Design/methodology/approach The study methodology encompassed literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…, 2011; Adi and Ni'am, 2012), Kuwait (Jarkas and Bitar, 2012), Nigeria (Nwosu, 2018), Qatar (Jarkas et al. , 2012), Sri Lanka (Manoharan et al. , 2022a) and Vietnam (Tuan and Tam, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…, 2011; Adi and Ni'am, 2012), Kuwait (Jarkas and Bitar, 2012), Nigeria (Nwosu, 2018), Qatar (Jarkas et al. , 2012), Sri Lanka (Manoharan et al. , 2022a) and Vietnam (Tuan and Tam, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Taking on the top 10 rankings of competencies in each category compared to past studies, most of those were found that substantially influenced the efficiency of construction activities in many nations, namely, Australia (Hughes and Thorpe, 2014), Egypt (Montaser et al, 2018), India (Shashank et al, 2014;Dixit et al, 2017;Murari and Joshi, 2019), Indonesia (Soekiman et al, 2011;Adi and Ni'am, 2012), Kuwait (Jarkas and Bitar, 2012), Nigeria (Nwosu, 2018), Qatar , Sri Lanka (Manoharan et al, 2022a) and Vietnam (Tuan and Tam, 2019). Taking on the methods for enhancing the critical competency elements of supervisory workers in construction, the relevant actions were identified through industry consultation discussions and literary analysis on the characteristics of those competencies and the current/future scopes of the industry practices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following the end of the protracted conflict of the "Elam war", the Sri Lankan construction sector saw tremendous expansion, drawing sizeable investments and employment opportunities connecting with various governmental and non-governmental bodies. As a result, the nation is currently undertaking a wide range of infrastructure development projects (Manoharan et al, 2022). However, the above-highlighted aspects have been the major causes that resulted in construction enterprises facing productivity-related problems in numerous infrastructure development projects in Sri Lanka (Kumara et al, 2018).…”
Section: Introductionmentioning
confidence: 99%